Indicators of Social Exclusion and Its Risks for Bedouin Youth in Ma'an Governorate: - - Abutayeh, Aydah Muhajer (Jordan Journal of Social Sciences, 2024)
This article aimed to identify the main indicators of social exclusion (including social, economic, and civil ones) as well as its risks for youth in Ma'an Governorate. To this end, the method of a social survey (a questionnaire) was followed. A proportional random sample of 315 males and females aged between 18 and 30 years was selected. The results indicated that the participants experienced social exclusion. Their family status demonstrates their low income, financial difficulties, and poor housing conditions, which all deprive young people of personal well-being. The employment status of the participants showed that 32% of them suffer from long-term unemployment and accumulated debts. Additionally, the results indicated that approximately 50% of the participants did not have training opportunities which would prepare them for different jobs. Furthermore, 72% of the participants did not participate in any cultural activities during the past five years, and they are found not to be affiliated with civil society. The participants held the government responsible for this exclusion. As for the risks of social exclusion, they were found to be high from the perspective of the participants. The most prominent risks include isolation, feelings of deprivation, and a tendency towards violence, which is exacerbated by ongoing financial hardship. The study recommended providing true training opportunities for young people in Ma’an governorate in order to prepare them with skills that help them secure a decent job. The study also recommended developing new policies that integrate Bedouin youth, particularly those who experience the long-term effects of unemployment.